Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1111/ics.12454
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to assess the effect of photodamage on corneocyte envelope maturity using combined hydrophobicity and mechanical fragility assays

Abstract: The combined method developed allows characterization of CE maturity based on hydrophobicity per unit surface area and rigidity rather than a simple ratio of lipid to involucrin. A more robust and sensitive measurement has therefore been developed addressing the limitations of earlier protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(50 citation statements)
references
References 26 publications
(67 reference statements)
2
41
2
Order By: Relevance
“…The presence of the eLOX3 antibody was ineffective in reducing the detected fluorescence which revealed that the inhibition by 12R‐LOX antibody is not owing to an unspecific spatial blockage by the antibody but an antigen‐specific blocking of 12R‐LOX. A parallel study investigated the impact of 12R‐LOX antibody in ex vivo CE maturation showing that CE rigidity improved while CE hydrophobicity remained unchanged in all tested samples (data not shown).The lower 12R‐LOX activity in PE samples is consistent with the reduced 12R‐LOX protein mass levels in PE cheek compared to PP post‐auricular sites as well as reduced CE maturation on this site . Decreased 12R‐LOX activity and reduced corneocyte maturation ex vivo demonstrate the importance of this enzyme for the SC maturation by influencing the CE hydrophobicity (D. Guneri, unpublished data).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…The presence of the eLOX3 antibody was ineffective in reducing the detected fluorescence which revealed that the inhibition by 12R‐LOX antibody is not owing to an unspecific spatial blockage by the antibody but an antigen‐specific blocking of 12R‐LOX. A parallel study investigated the impact of 12R‐LOX antibody in ex vivo CE maturation showing that CE rigidity improved while CE hydrophobicity remained unchanged in all tested samples (data not shown).The lower 12R‐LOX activity in PE samples is consistent with the reduced 12R‐LOX protein mass levels in PE cheek compared to PP post‐auricular sites as well as reduced CE maturation on this site . Decreased 12R‐LOX activity and reduced corneocyte maturation ex vivo demonstrate the importance of this enzyme for the SC maturation by influencing the CE hydrophobicity (D. Guneri, unpublished data).…”
Section: Discussionmentioning
confidence: 67%
“…The importance of these metabolic products, their formation and role in CLE formation was highlighted by the work of Brash and collaborators who focused on 12R‐LOX as the first enzyme in ceramide EOS linoleate oxidation . However, we were interested in this enzyme because of the known reduced maturation of facial SC corneocytes as reduced mass levels of 12R‐LOX were recently reported in Caucasian facial SC . This finding was accompanied with lower 12R‐LOX mass levels in Albino Africans compared to Black Africans and Caucasians .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…With the tactile working principle of AFM, mechanical properties like rigidity (Young's modulus) became accessible on subcellular level and have been reported for corneocytes as well . While dry corneocytes conceivably are more rigid than living keratinocytes (water makes soft), it is not predictable, how the contributions of cytoskeletal fibres or proteins or lipid mixture alter their rigidity in diseased states.…”
Section: Ex Vivo Methods For Barrier Assessmentmentioning
confidence: 99%